Estudio de factibilidad para el establecimiento de una línea de crédito para el desarrollo de la población con capacidades especiales en edad de trabajar de la ciudad de Quevedo. - Garcés Santana, Gustavo Adolfo (2015)
The bank has prioritized lending to commercial activities, services, industry, export agriculture, handicrafts, among others, and to a lesser extent with micro- social. In Quevedo there is no bench capable of integrating social guidance to families who have family members with special needs, giving them credit and make them economically productive. The main cause of disability in Quevedo is the product of illness, expressed as 29.92 % of respondents. Of a special skills, 38.01 % is physical in nature, followed by 17.79 % with visual disabilities…..